Incidence of major and clinically relevant non-major bleeding in patients prescribed rivaroxaban for stroke prevention in non-valvular atrial fibrillation in secondary care: Results from the Rivaroxaban Observational Safety Evaluation (ROSE) study - Evans, Alison; Davies, Miranda; Osborne, Vicki; Roy, Debabrata; Shakir, Saad (PloS one, 2020)
Although the direct oral anticoagulant rivaroxaban is recommended for stroke prevention in patients with non-valvular atrial fibrillation based on Phase III clinical trials, there is still a need for additional safety data from everyday clinical practice. The ROSE study was initiated to collect further information on the safety and utilisation of rivaroxaban in a broader range of patient groups in routine clinical practice. The ROSE study was conducted in hospitals in England and Wales. Consenting adults with non-valvular atrial fibrillation newly started on rivaroxaban were eligible and followed up for 12 weeks. Data was derived through secondary use of medical records. The primary outcome was major bleeding within gastrointestinal, urogenital and intracranial sites. A total of 4846 patients were enrolled in the study September 2013 to January 2016, 965 of which were treated with rivaroxaban for non-valvular atrial fibrillation. The median age in the rivaroxaban non-valvular atrial fibrillation cohort was 76 years, 53.6% were male. The median HAS-BLED score was 2 and the median CHA2DS2-VASc score was 4. The risk of major bleeding within each of the primary sites of gastrointestinal, urogenital and intracranial during the 12 week observation period was low (0.2%; n = 2). The risk of major bleeding in all sites was 1.0% (n = 10) at a rate of 5.5 events per 100 patient years. In terms of the primary outcome risk of major bleeding within gastrointestinal, urogenital and intracranial sites during the 12 week observation period, the risk estimates in the non-valvular atrial fibrillation rivaroxaban user population were low (<1%), and consistent with risk estimated from clinical trial data and in routine clinical practice.